Weight-length relationships and weight conversion factors in two stocks of megrim (Lepidorhombus whiffiagonis): Celtic Seas - northern Bay of Biscay (7.b-k, 8.abd stock) and northern Iberian waters (8.c, 9.a stock) - Landa, Jorge; Korta, María; Iriondo, A.; Fontenla-Giráldez, Jorge; Gancedo, Rosa María; Rodríguez-Fernández, Lorena; Reparaz, María; Loureiro-Caride, María Isabel; Gómez-González, Antonio; Castro-Loehmann, Begoña; Antolínez, Ana; Bruno, Isabel; et al. (2022)
BIOBENTON-4 Biología de especies bentónicas comerciales (rape blanco, rape negro, gallo del norte, gallo, cigala y cuco) en el área del ICES